Atiya: the most iconoclastic of the Fyzee sisters - Hasan, Md. Mahmudul (2020)
The Fyzee sisters were ahead of their time in their views and ways of life. However, given the unconventionality, unique personality and independence of spirit, Atiya was the most iconoclastic of them all. Atiya was unconventional and “unorthodox” in her behaviour in more than one sense. At a time when female education was at best rudimentary and at worst scorned and ridiculed, or in many cases discouraged or restricted to the home, she made a transcontinental trip for educational purposes at the age of 29 and unmarried. As mentioned before, she travelled extensively within the borders of South Asia and across the globe at a time when transnational journeys were not a smooth or easy affair, especially for women.